STRUKTUR PENYAJIAN TARI LANGKAH 12 DI DESA BALAI SEBUT KECAMATAN JANGKANG KABUPATEN SANGGAU - Tita Oktaviani; Imma Fretisari; Chiristianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research problem is related to the Tari Langkah 12 Presentation Strcture in Balai Sebut kecamatan Jangkang Kabupaten Sanggau. This study aims to describe the structure of the presentation of  Tari Langkah 12 in Balai Sebut Kecamatan Jangkang Kabupaten Sanggau. The method used is descriptive method with a qualitative form and choreograpic approach. The data of this research is to find out the overall structre of  Tari Langkah 12 from the composision of a presentation. Data collection techniques are triangulation, observation, interview, and documentation to the speakers Sdarmodjo, Mustafa Tomik and Abang Sahl Nizam. Data analysis techniqes include data redction, data presentation and verification. Based on the results of the study concluded with that Tari Langkah 12 is expected to appear in the 1940s. Motion is divided into three namely there are initial movements, middle movements (contests) and closing motion and connecting monition. Three are supporting elements of dance, namely clothing,cosmetology, music The results of the study can be a material for teachers to handle or teaching matetials in schools in learning Cultural Arts.    Keywords: Presentation Structure, Tari Langkah 12